Modeling of Minimum and Maximum Void Ratios of Granular Soils. (20th February 2021) - Qian, Xiaoxu; Liu, Xin; Shao, Zhiwei; Shi, Yunqiang; Zhang, Siqing; Hong, Baoning
Abstract : Determining the maximum and minimum void ratios of granular soils is very important because it can be correlated with engineering behaviors such as soil permeability. Empirical relationships can be used for determining the void ratio, but they have many limitations related to the shape and the size distribution of the grains. Analytical methods improve the empirical relationships. In this paper, we present enhancements to the model of Chang et al. by combining the model of Youd et al., as Chang–Youd models, to make it more convenient and also to extend its usage to be suitable for determining the maximum void ratio. The Chang–Youd models are verified with experimental tests performed by the authors. Compared with the experimental results in the literature, the Chang–Youd models are also effective but more convenient and practical.